Placenta response of inflammation and oxidative stress in low-risk term childbirth: the implication of delivery mode - Yabin Hu; Kun Huang; Yuanfang Sun; Jianqing Wang; Yeqing Xu; Shuangqin Yan; Peng Zhu; Fangbiao Tao (BMC, 2017)
Abstract Background Caesarean delivery rate is increasing gradually in China and there is no doubt that delivery mode is closely associated with the maternal health and infant development.This study examined the independent effect of delivery mode on placenta inflammation response and oxidative stress response. Methods A total of 3474 pregnant women recruited in Ma'anshan Birth Cohort Study were the initial study population. Data on maternal socio-demographic characteristics and pre-pregnancy BMI were collected at their 1st antenatal checkups. Pregnancy-specific anxiety was assessed during the three trimesters of pregnancy. Common pregnant complications were monitored in the whole pregnancy period. Delivery modes, as well as newborn characteristics were abstracted from medical records. Delivery modes included vaginal deliveries (VD), caesarean delivery with medical indications (CDMI), caesarean delivery on maternal request (CDMR) and urgent cesarean delivery (UCD). Placentas were collected during childbirth. The mRNA expression of IL-1β, TNF-a, IL-6, IFN-γ, IL-4, IL-10, IL-8, and HO-1 were assessed in the final sample of 1978 low-risk women with singleton term-births. Results The overall rate of caesarean delivery (CD) was 50.5% (1650/3265) in singleton term childbirths in this study. Among women who reported definite CD reasons, 56.8%of them chose the surgery without any medical indications.It shows a non-linear relationship between cytokines related with placenta inflammatory response, oxidative stress response and different delivery modes. At high percentiles of IL-1β, IFN-γ and IL-8, women with CDMR had higher expression levels compared to women with VD. Women with CDMI had higher levels at median percentiles of IL-1β, IFN-γ and IL-8. Women with CDMR had higher expression compared with VD at high percentiles of IL-6 and HO-1, and women with CDMI had higher levels of these two cytokines at their low percentiles. It is worth noting that at high percentiles, compared with normal delivery, the expression of IL-1β, IFN-γ, IL-8 and HO-1 have significantly altered in women with CDMR. Conclusion A high overall CD rate was found in this study, and caesarean delivery on maternal request was the major contributor to the high prevalence. Maternal placental oxidative stress and inflammatory response were closely associated with delivery mode. The effect is much amplified at high levels of expression in women who chose CD on maternal request.Such difference needs to be noticed and may have important implications for obstetricians, midwives and other perinatal health care workers.